Three stages of ductile fracture process in commercial carbon steel - Šiđanin, Leposava; Drobnjak, Đorđe (Journal of Production Engineering, 1984)
Uniaxial tensile ductility and fracture of a commercially hot rolled steel wire were investigated with a special emphasis on elongated MnAl stlicate inclusions by electron micro analysts and scanning electron microscopy. In the course of plastic deformation, extensive cracks develop from the cracking of the MnAl-state and cohesion of the MnAl silicate matrix interface. These cracks grow to a size comparable to that of MnAl-silicate inclusions themselves. Elongated MnAl inclusions have been understood to impose geometrical direction to accelerate final fracture either by the process of microvoids coalescence associated with submicron spherical inclusions or linking up by shearing. Based on these observations, a model for crack and propagation is proposed.